2015
DOI: 10.1177/0022034515613508
|View full text |Cite
|
Sign up to set email alerts
|

Excess BMP Signaling in Heterotopic Cartilage Forming in Prg4-null TMJ Discs

Abstract: Heterotopic cartilage develops in certain pathologic conditions, including those affecting the human temporomandibular joint (TMJ), but the underlying molecular mechanisms remain obscure. This is in part due to the fact that a reliable animal model of such TMJ diseases is not available. Here, we show that aberrant chondrocyte differentiation and ectopic cartilage formation occur spontaneously in proteoglycan 4 (Prg4) mutant TMJ discs without further invasive procedure. By 2 mo of age, mutant disc cells display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Cultures were prepared from glenoid fossa/eminence samples isolated from 2 month-old wild-type mice (n=32) as described (Bechtold et al, 2015) with some modifications. Isolated glenoid fossae were incubated with 2.5 U/ml dispase (MP Biomedicals, LLC, Solon, OH) and 600 U/ml (3mg/ml) type I collagenase (Worthington Biochemical Corporation, Lakewood, NJ) in HBSS with Ca 2+ and Mg 2+ for 10 min at 37°C with agitation, and then the surface was curetted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultures were prepared from glenoid fossa/eminence samples isolated from 2 month-old wild-type mice (n=32) as described (Bechtold et al, 2015) with some modifications. Isolated glenoid fossae were incubated with 2.5 U/ml dispase (MP Biomedicals, LLC, Solon, OH) and 600 U/ml (3mg/ml) type I collagenase (Worthington Biochemical Corporation, Lakewood, NJ) in HBSS with Ca 2+ and Mg 2+ for 10 min at 37°C with agitation, and then the surface was curetted.…”
Section: Methodsmentioning
confidence: 99%
“…(Hill et al, 2014; Koyama et al, 2014). We also reported that Prg4 -null mice displayed increased levels of chondrogenesis and ectopic cartilage formation within TMJ components (Bechtold et al, 2015; Koyama et al, 2014), but the cellular, signaling and molecular mechanisms underling such potentially important pathogenic transformation remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Results from this study illustrate that BMP-2 treatment potentiated the induction of Acan, Col2 , Col 10 , and Ihh in Bgn −/− Fmod −/− mice. Excess BMP-2 signaling has also been implicated in the pathogenesis of accelerated TMJ-OA in Pgr4-KO mice [Bechtold et al 2016]. In contrast, absence of BMP signaling in transgenic mice with Bmp1Ra conditionally deleted in neural crest cells led to failure of articular disc separation from the hypoplastic condyle and under development of the mandibular condylar cartilage [Gu et al 2014].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal activation of this signaling causes heterotopic cartilage and bone formation [Huegel et al 2015, Billings et al, 2008]. Specifically, excessive BMP-2 signaling has recently been shown to be involved in heterotopic cartilage formation and the pathogenesis of TMJ-OA [Bechtold et al 2016, Albilia et al, 2013]. However, the mechanism of excessive BMP-2 signaling on the mandibular condylar cartilage and its implications in TMJ-OA are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In seeking for effective treatment and functional repair strategies, murine model becomes a necessary and unique in vivo platform, as its availability for genetic modification and short lifespan enable pinpointing the TMJ development, biology and pathogenesis to specific molecules or signaling pathways (Suzuki and Iwata, 2016). Evaluation of the phenotype in genetically modified mice has provided new insights into the roles of individual matrix molecules in TMJ development and OA, such as lubricin (Bechtold et al, 2016; Hill et al, 2014; Koyama et al, 2014), biglycan and fibromodulin (Wadhwa et al, 2005), collagen types II (Ricks et al, 2013) and XI (Xu et al, 2003). In addition, aided by clinically relevant operations such as partial discectomy (Xu et al, 2009) and anterior crossbite prosthesis (Liu et al, 2014), TMJ OA can be induced in mice to study the disease initiation and progression in a well-defined timeframe in vivo.…”
Section: Introductionmentioning
confidence: 99%